Study and evaluation the air pollution around the thermal power plant of Zebadiah city, Wassit province, Iraq - Kamal Mahmood, Abdulkhaleq; Abdulkhaleq Kamal, Ali (International Journal of Engineering and Technology, 2018)
This study focused on gaseous pollution caused by exhaust gas from AL-Zubaydiah thermal power plant. Study gases included sulfur dioxide (SO2), nitrogen oxide (NO), carbon oxide (CO) and hydrocarbon (HC). The concentration of gas measurement is conducted during six months from January until June 2017. Nova 600 series portable devise and G450 confined space gas detector was used for measuring gas concentration, which emitted from the chimney of the thermal power station with an interval of 100m and into the path of smoke for a distance of 1400 m. The prevailing wind direction and temperature were taken into consideration during the study and their impact on the gas distribution. Four readings have been taken in each station during each month for all gases under study. The results showed that less gas concentrations were near the power station and then getting more gas concentration away from the station and higher concentrations are obtained at a distance of 900 m from the power station at ground level. Results indicated that sulfur dioxide concentrations recorded were higher than allowed in the Iraqi and American standards in most locations around the station. The highest concentration recorded at 900 m from the power station with value 597.3968 Î¼g/m3, which is higher than the limitation of Iraqi and international specifications (150 Î¼g/m3). This high concentration of SO2 is due to the crude oil from the Ahdab field with high rates of Sulphur that used as fuel in the generation process. These high concentrations of sulfur dioxide cause problems on the growth of plants and human health and viability of the soil in the coming years. Nitrogen oxide gas concentrations also were high and outside the upper limits allowed and were worth 131.38 Î¼g/m3. The rest of the gas concentration (CO and HC) were acceptable and within the Iraqi standard. To preserve the environment in the region and within the limits of the allowed values globally requires a search for another source of fuel with a low percentage of sulfur and using modern technology for burning to reduce emissions of nitrogen oxides.Â Â